Alignment of the Irish legal system and Article 13.1 of the CRPD for witnesses with communication difficulties - Catherine O'Leary; Michael Feely (Disability Studies Quarterly, 2018)
Irish and international legal reform resulting from the Convention on the Rights of Persons with Disabilities [CRPD] has primarily focussed on Article 12, the right to exercise legal capacity. Article 13, which declares the right to access justice and the right to access procedural accommodations for all with disabilities, is often neglected. Specifically, research has not sufficiently explored the accommodations needed by witnesses with communication difficulties to testify in the courtroom. This study brings this aspect of Article 13 into focus by exploring the views of Irish legal professionals and disability advocates regarding existing and potential further accommodations for witnesses with communication diffiuclties in Irish criminal proceedings. By comparing and contrasting contributions, a series of conflicting perspectives between the legal profession and disability community are revealed. As successful implementation of Article 13 requires collaboration between both groups, this study concludes that these conflicts will need to be acknowledged and addressed in order for reform of courtroom accommodations to succeed.